STRATEGI PEMBERDAYAAN PETANI PADI RAWA LEBAK MELALUI PENINGKATAN PENGETAHUAN DAN SIKAP (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2020)
Lowland swamps can be developed as agricultural land with potential competitiveness that can be cultivated in the dry season and the rainy season so that there is an increase in the cropping index that can improve the welfare of farmers. South Sumatra Province has large swamp lands, one of which is in Ogan Komering Ilir Regency ( OKI). However, the productivity of rice in this area is still quite low so that it has the opportunity to be improved by improving the technology of lowland rice cultivation. This study aims to: (1) identify the application of lowland swamp rice cultivation technology at the farmer level, and (2) analyze the level of knowledge and attitudes of farmers towards lowland swamp rice cultivation technology. The assessment was carried out from January to May 2019 in Sugiwaras Village, Teluk Gelam District, Ogan Komering Ilir Regency with 22 farmers as respondents. Respondents were selected by purposive sampling method. The results of the study show that: (1) The application of lowland swamp rice cultivation at the farm level (existing) is still relatively simple with good levels of application, namely seeding, land preparation, tillage and weed control; (2) Knowledge of farmers increased by 41.42% supported by a positive attitude of farmers towards disseminated swamp rice cultivation technology. Keywords: Empowerment, knowledge, farmers, swamps, attitudes